EVALUASI PASCA PELATIHAN PENCEGAHAN DAN PENGENDALIAN INFEKSI TENAGA KESEHATAN PUSKESMAS: PENDEKATAN MODEL KIRKPATRICK - Tuti Surtimanah; Setia Kahadiwan; Ade Ana Asmara; Irna Avianti; Irfan Nafis Sjamsuddin (Jurnal Sehat Masada, 2026)
Background: Post-training evaluation is essential to assess the effectiveness of health training programs, particularly in ensuring behavioral change and workplace impact. This study aimed to evaluate post-training evaluation of Infection Prevention and Control (IPC) training based on the Kirkpatrick Model, particularly at the behavior and results levels, and to identify factors influencing post-training behavioral change. Methods: A quantitative evaluative cross-sectional design was employed. Respondents included IPC training alumni, their direct supervisors, and co-workers working in primary health centers across 10 districts/city in West Java Province. Data were collected using structured questionnaires and analyzed through descriptive statistics, difference tests, correlation analysis, and regression. Results: The alumni demonstrated high levels of knowledge, attitudes, and skill application; however, post-training behavioral change scores were relatively lower. Implementation of the Follow-up Plan showed a strong and consistent association with post-training behavioral change and emerged as the only significant predictor in the linear regression model. The logistic regression model revealed that self-assessment, action plan implementation, and enabling factors jointly contributed to a higher likelihood of behavioral change, although none were individually significant. Conclusion: This study concludes that behavioral outcomes of IPC training are largely determined by effective implementation of Follow-up Plans and supportive workplace environments. Strengthening the Action Plan mechanisms and integrating post-training evaluation based on the Kirkpatrick Model are therefore essential for enhancing the effectiveness and sustainability of health training programs.